Pete the cat and his four groovy buttons ebook - Litwin, Eric (Pete the Cat., 2012)
An award-winning and bestselling Pete the Cat hardcover picture book! Count down with Pete in this rocking story that makes counting fun! Pete the Cat is wearing his favorite shirt—the one with the four totally groovy buttons. But when one falls off, does Pete cry? Goodness, no! He just keeps on singing his song—after all, what could be groovier than three groovy buttons? This book is a winner of the Theodor Seuss Geisel Honor Award. Plus the fun never stops—download the free groovin' song! Don't miss Pete's other adventures, including Pete the Cat: I Love My White Shoes, Pete the Cat: Rocking in My School Shoes, Pete the Cat Saves Christmas, Pete the Cat and His Magic Sunglasses, Pete the Cat and the Bedtime Blues, Pete the Cat and the New Guy, Pete the Cat and the Cool Cat Boogie, Pete the Cat and the Missing Cupcakes, Pete the Cat and the Perfect Pizza Party, and Pete the Cat: Crayons Rock!